A Novel RP-HPLC Method for the Simultaneous Analysis of Some Active Ingredients in Cough-Cold Syrup Formulation - Zor, Sule Dinc; Donmez, Ozlem Aksu; Asci, Burge; Yarkadas, Gizem (BENTHAM SCIENCE PUBL LTD, 2017)
Background: This study deals with the development of an RP-HPLC method for paracetamol (PAR), guaifenesin (GUA), phenylephrine hydrochloride (PEH), and pyrilamine maleate (PAM) in a commercial syrup formulation using experimental design. Methods: For the determination of optimum chromatographic conditions, Box-Behnken design used four variables at three levels was applied. The variables investigated were pH, flow rate and phosphate buffer percentages in the mobile phase. Resolution between adjacent peaks was chosen as a response to the experimental design. Stationary phase was Inertsil (octadecylsilane) ODS-3 C18 column with the dimensions (250 4.6 mm, 5 mu m) dimensions. Detection was carried out using a variable-wavelength UV-Vis detector at 250 nm for PAR and at 220 nm for others. The optimum conditions were: pH 3.5, 95% and 80% phosphate buffer for gradient elution, and 0.8 mL/min flow rate. The method was validated as per ICH guidelines. The limit of detection and limit of quantitation were 0.32 mu g/mL and 1.07 mu g/mL for PAR, 0.25 mu g/mL and 0.83 mu g/mL for GUA, 0.34 mu g/mL and 1.14 mu g/mL for PEH, and 0.42 mu g/mL and 1.41 mu g/mL for PAM, respectively. The method was linear with regression coefficient values between 0.9997 and 0.9999. For all the four active compounds, the precision values (inter-day and intra-day) based on the relative standard deviation ranged from 0.18% to 1.98% and accuracy ranged from 98.93% to 104.30%. The developed method was succesfully applied for the analysis of a syrup formulation containing PAR, GUA, PEH and PAM combination.
Keywords: Box-Behnken design; paracetamol; guaifenesin; phenylephrine hydrochloride; pyrilamine maleate; RP-HPLC method; syrup formulation; SIMULTANEOUS SPECTROPHOTOMETRIC DETERMINATION; PERFORMANCE LIQUID-CHROMATOGRAPHY; MASS-SPECTROMETRY METHOD; PHARMACEUTICAL FORMULATIONS; CHLORPHENIRAMINE MALEATE; EXPERIMENTAL-DESIGN; HUMAN PLASMA; PSEUDOEPHEDRINE HYDROCHLORIDE; CAPILLARY-ELECTROPHORESIS; Pharmacology & Pharmacy